Kewajiban Rehabilitasi bagi Pecandu Narkotika berdasarkan Putusan Hakim - Antonius Aditya Pratama (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Law Number 35 of 2009 concerning Narcotics has regulated the opportunities for medical rehabilitation and social rehabilitation for addicts and victims of narcotics abuse, as described in Article 54, Article 55, Article 103 and Article 127 Paragraphs (1), (2) and (3). In addition, it is also regulated in Articles 13-14 of Government Regulation Number 25 of 2011 concerning the Implementation of Compulsory Reporting of Narcotics Addicts and also the Circular Letter of the Supreme Court (SEMA) Number 4 of 2010 concerning Placement of Abuse, Victims of Abuse and Narcotics Addicts into Medical Rehabilitation and Rehabilitation Institutions. Social. The problems studied in this paper are how to regulate the implementation of rehabilitation for narcotics addicts based on the judge's decision and how the role of the competent agency in the implementation of rehabilitation for narcotics addicts is based on the judge's decision. Provisions for rehabilitation for narcotics abusers are regulated in Law No. 35 of 2009, it is stated in Article 54 that Narcotics Addicts and Narcotics Victims are required to undergo medical and social rehabilitation. This is clarified in Article 3 paragraph (1) of the Regulation of the Head of the National Narcotics Agency Number 11 of 2014 concerning Procedures for Handling Narcotics Addicts and/or Defendants of Narcotics Addicts and Victims of Narcotics Abusers in Rehabilitation Institutions (BNN Regulation 11/2014) which stipulates that Narcotics Addicts and Victims of narcotics abusers who are without rights and against the law as suspects and/or defendants in narcotics abuse who are undergoing the process of investigation, prosecution, and trial in court are given treatment, care and recovery in rehabilitation institutions. At the time the judge decides on rehabilitation, the judge will determine whether the person concerned (in this case the Narcotics Addict) undergoes rehabilitation or not based on whether or not the crime committed is proven. This is regulated as in Article 103 of Law no. 35 of 2009 concerning Narcotics. The Role of Agencies in the Rehabilitation of Narcotics Addicts in the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics as a non-penal effort of the National Narcotics Agency is the implementation of mandatory reporting of Narcotics addicts, Recipient institutions must report (IPWL) Narcotics addicts, Medical rehabilitation, Social rehabilitation